Peran Interprofesional Education Dalam Pengembangan Kompetensi Mahasiswa Keperawatan: Literature Review - Siti Zahara Nasution; Shofi Auliya Sari Nasution; Evi Karota Bukit; Rika Endah Nurhidayah (STIKES Columbia Asia Medan, 2026)
Introduction: Interprofessional Education (IPE) is an important learning approach in nursing education because healthcare services require effective interprofessional collaboration. Nursing students need to be prepared during their education to communicate effectively, understand the roles of other professions, work in teams, and provide patient-centered care. This study aims to examine the role of IPE in developing collaborative competence among nursing students. Methods: This study used a systematic literature review method based on the PRISMA flow. Articles were searched through Google Scholar, PubMed, ScienceDirect, BMC, and Springer. The inclusion criteria were articles published from 2021 onward, available in full text, written in Indonesian or English, primary research articles, discussing IPE, involving nursing students or health students with nursing student participation, and having outcomes related to collaborative competence. Data were extracted using a matrix table and analyzed using a descriptive narrative approach to compare study characteristics, types of interventions, instruments, and main findings. Results: A total of 10 articles were analyzed, consisting of 5 Indonesian articles and 5 international articles. The findings showed that IPE had a positive role in improving interprofessional communication, teamwork, understanding of roles and responsibilities, conflict management, team functioning, readiness for interprofessional learning, and collaborative competence. Active learning methods such as interprofessional simulation, role play, case studies, cross-professional programs, and service-learning provided students with direct experiences to collaborate, reflect on professional roles, and make shared decisions in clinical learning situations. Conclusion: IPE plays an important role in developing collaborative competence among nursing students. The structured implementation of IPE in the nursing curriculum is needed to prepare students for clinical practice and to work effectively in complex, safe, and patient-centered interprofessional teams.